STRUGGLE FOR RIGHT IN JODY'S PICOLT MY SISTER KEEPER:AN INDIVIDUAL PSYCHOLOGICAL APPROACH - RATNASARI, IKHA YOGA (2011)
The object of the research in the novel entitled My Sister Keeper bu Jody Picoult. The study focuses on the major character, Anna Fitzgerald in facing her struggle to get her right in medical emancipation from her parents. The aims of the study are: 1) To analyze the novel based on the structural element of the novel, 2) To analyze the major character based on the individual psychological perspective. The study uses qualitative study, in this method the research uses two data source, namely primary and secondary data source. The primary data source and the object of the study are the novel My sister Keeper. While the secondary data source are, any books of literature and psychology related to this study. The result of the analysis shows the following conclusion. Firstly, the structural element of the novel presents a good unity, Jody Picoult's employs traditional plot, beginning from the exposition followed by complication, climax and resolution. She tries to give a moral message through this novel that 'people should struggle and sacrifice to get their own right for better life". She employs from each chapter in the book told from first person point of view. She also uses style in writing. Secondly, the result of the individual psychology analysis shows that Anna's personality changes from weak girl into strong girl to struggle to get her right.